Fight for the green earth: The existence of local knowledge in agriculture. Issue 1 (March 2020) - Halim, H; Bahri, S; Zainuddin, R; Kamaruddin, S A; Anriani, H B
Abstract: Traditional agriculture has always been taking place in rural areas. This agricultural model tends to utilize simple technology and is in accordance with local socio-cultural conditions. The traditional agricultural model is also the opposition of modern agriculture in the concept of a green environment or green earth. If modern agriculture has many negative impacts on the environment, then traditional agriculture has many positive impacts on the lives of all earthly creatures. This paper aims to reveal the actions of farmers in managing their agricultural land based on local knowledge. This research took place in three locations, namely: (1) Labuku Village, Maiwa District, Enrekang Regency, (2) Ilan Batu Village, Walenrang Barat District, Luwu Regency, (3) Segeri Village Segeri District, Pangkep Regency. The informants of this study were farmers in the three regions. Each region has 2 informants so that the total was 6 informants. The key informants are each of the traditional leaders, and village officials. Data collection using interview techniques, observation, and study of literature. Data analysis uses Three-Flow techniques namely reduction, categorization, and conclusion. The results showed that traditional farming techniques in Labuku, Ilan Batu, and Segeri Village were characterized by rain-fed rice fields, not using chemical fertilizers as plant fertilizers, rice disease repellent, and rat repellent but instead using betel leaves, betel nuts, and lime. Even so, high-quality rice is harvested once a year. The conclusion of this research is that traditional knowledge-based agriculture in the research location always uses the surrounding environment resources. Such methods directly impact on the creation of a green environment and indirectly counteract the negative impacts of modern agriculture.